Detection of Staphylococcus aureus Enterotoxin A (SEA) Using Dot-ELISA in Milk Samples - Haniyeh Golafrouz; Hamed Ahari; Seyed Amirali Anvar; Delavar Shahbazzadeh (Pasteur Institute of Iran, 2020)
Introduction: Staphylococcus aureus enterotoxin A (SEA) is one of the most common causes of staphylococcal food poisoning. Due to the simplicity and no requirement for laboratory apparatuses, dot-ELISA is a choice method for detecting Staphylococcal enterotoxins. The present study aimed to develop a dot-ELISA for the detection of SEA. Methods: Nitrocellulose membranes were coated with the SEA antibody and blocked by the addition of 3% bovine serum albumin (BSA) blocking buffer. After 1 h incubation and washing the membranes, milk samples and the positive control (SEA, 50 ng/ml) were added to the membranes and incubated for 1 h. The membranes were then washed and incubated for 45 min with HRP-conjugated SEA, followed by the addition of TMB. Results: Our dot-ELISA could detect amounts of ≥ 50 ng/ml of SEA in the milk samples. Of the 30 raw milk samples randomly purchased from dairy product stores in District 3, Tehran, 5 (16%) contained SEA ≥ 50 ng/ml by the dot-ELISA. Conclusion: The dot-ELISA showed to be a reliable method for the preliminary screening of milk samples for SEA contamination. This method is cost-effective, fast, and does not require an ELISA-reader device.